Reversed Size, Book-to-Market and Momentum Effects: A Review of Malaysian Equity Returns Behavior - Gunathilaka, Chandana; Jais, Mohamad; Balia, Sophee Sulong; Abidin, Azlan Zainol; Abdul Manaf, Kamarul Bahrain (Advanced Science Letters, 2017)
This paper reviews behavior of widely documented equity market return anomalies and their pricing implications in multifactor asset pricing models. We apply time series and panel tests for 24 risk—mimicking portfolios, formed over a period of 14 years.In contrast to prior findings in Malaysia, we report evidence of small firm discount, together with persisting significance of the size effect.Evidence suggests that liquidity is the source of small discount.BM effect remains significant in explaining equity returns. Regardless of the evidence of short-term momentum trading profits, we dismiss application of a risk factor to the effect of momentum anomaly.Fama-French three-factor model, while efficient than CAPM, leaves a substantial unexplained component. The paper provides insights of the source of the size effect in equity returns, and pricing debate in Malaysian market.